Geoheritage - Donaldson, J. (Geoscience Canada, 2008)
SUMMARY Geoheritage, a word that embraces recognition of the continuum between the geological record and cultural values, has gained widespread usage during the past three decades in Europe and Australia, and has attained increasing acceptance since the turn of the century in Asia and North America. By drawing attention to the value of society’s understanding of the processes responsible for landscape development as it contributes to an aesthetic appreciation of nature, as well as for practical applications such as mitigating geohazards, this term provides a useful overture to encourage public awareness of the origin, evolution and significance of the abiotic components of our planet. In addition to this educational aspect, the term also provides a focus for establishing and nurturing programs dedicated to geopreservation and geoconservation.